Influence of arbuscular mycorrhizal fungus Glomus intraradices on accumulation of radiocaesium by plant species - Dubchak, S.V. (Проблеми безпеки атомних електростанцій і Чорнобиля, 2012)
The role of arbuscular mycorrhizal fungus Glomus intraradices in ¹³⁴Cs isotope uptake by different plant species is studied. The impact of radiocaesium on mycorrhizal development and functioning of plant photosynthetic apparatus is considered. The possibility of mycorrhizal symbiosis application in phytoremediation of radioactively contaminated areas is analyzed. It is found that colonization of plants with arbuscular mycorrhizal fungus resulted in significant decrease of radiocaesium concentration in their aboveground parts, while it did not have considerable impact on the radionuclide uptake by plant root system.